2019
DOI: 10.3390/s19163531
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Computational Methods for Compressed Sensing Reconstruction of EMG Signal

Abstract: Wearable devices offer a convenient means to monitor biosignals in real time at relatively low cost, and provide continuous monitoring without causing any discomfort. Among signals that contain critical information about human body status, electromyography (EMG) signal is particular useful in monitoring muscle functionality and activity during sport, fitness, or daily life. In particular surface electromyography (sEMG) has proven to be a suitable technique in several health monitoring applications, thanks to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…EEG signal is carried out when an instruction is transmitted to or received from emotional, visual, auditory, sensory, or muscular stimuli. Therefore, the research in the EEG signal is carried out in various fields such as robotics, medical engineering, and image processing [ 39 , 40 , 41 ]. EEG signal is used to recognize the voice by measuring its frequency through potential differences generated from the temporal lobe [ 8 , 9 ].…”
Section: Biosignal-based Speech Recognitionmentioning
confidence: 99%
“…EEG signal is carried out when an instruction is transmitted to or received from emotional, visual, auditory, sensory, or muscular stimuli. Therefore, the research in the EEG signal is carried out in various fields such as robotics, medical engineering, and image processing [ 39 , 40 , 41 ]. EEG signal is used to recognize the voice by measuring its frequency through potential differences generated from the temporal lobe [ 8 , 9 ].…”
Section: Biosignal-based Speech Recognitionmentioning
confidence: 99%
“…Electromyography (EMG) is a diagnostic method, which enables recording of bioelectric signals resulting from the activities of the skeletal muscles [ 2 , 3 ]. It is often performed while stimulating the relevant motor and peripheral nerves.…”
Section: Electromyographymentioning
confidence: 99%
“…In order to make such systems efficient compressed sensing, or compressive sampling (CS), is applied. The CS is a method for data acquisition, where only few incoherent measurements are required in order to compress sparse in some domain signals [ 3 , 11 , 12 , 13 ]. In [ 11 , 12 , 13 ], the authors showed interesting solutions for compressing both ECG (electrocardiography) and EMG data.…”
Section: Electromyographymentioning
confidence: 99%
See 1 more Smart Citation
“…The advances in deep learning allows extracting features from signals that was not possible using conventional algorithms due to artefacts and noise. This also has been experienced with the use of AI for extracting meaningful signals from electromyography (EMG) measurements [8].…”
Section: Review Of the Contributions In This Special Issuementioning
confidence: 99%